The Effect of Government Accounting Standards, Utilization of Information Technology, and Accounting Internal Control on the Quality of Financial Reports with Organizational Commitments as Moderating Variables - Indriyani, Dewi; Mappanyukki, Ratna (JURNAL AKUNTANSI DAN AUDITING, 2021)
Research aims: This study identifies the effect of applying government accounting standards; implement the information technology; and internal control system of accounting on the quality of financial reports with the moderating variable is organizational commitment.Design/Methodology/Approach: The study implemented a quantitative approach with a purposive sampling technique on 100 respondents of the State Civil Apparatus within the Ministry of Religion that comprises 53 central employees and 47 provincial employees. Collecting primary data was conducted by filling out a questionnaire. Hypothesis testing utilized bootstrapping procedure.Research findings: The results showed that the application of government accounting standards is accrual based; Utilization of Information Technology; and Accounting Internal Control have positive and significant influences on the Quality of Financial Reports. Then, organizational commitment does not act as moderation to the influence between the application of government accounting standards and the quality of financial reports. However, organizational commitment can moderate the influence between the use of information technology and the quality of financial reports, internal control and the quality of financial reports significantly